Circo-suporte: por uma poética material no circo contemporâneo - Pinheiro, Iago Domingos Bezerra (2024)
The research "Circus-Support: towards a material poetics in contemporary circus" aims to reflect on the scenic-dramaturgical possibilities of the circus spectacle, starting from the concept of displacement of the circus object and function/technique. We intend to trace the idea of how the use of support in the circus is directly related to the corporeality of the artists on stage, presenting at the end the possibility of the Circus-Maquette resource as a circus artistic object in itself, as well as part of the methodological procedures for the elaboration of circus spectacle dramaturgy. To do so, we will investigate how the logic of the circus attraction influenced the movement of Russian Constructivism, how the processes of 'artification' occur and have occurred based on the conceptualization of Nathalie Heinich and Roberta Shapiro, addressing the theme of the formation movement of circus schools, based especially (but not exclusively) on examples from experiences developed in the Soviet Union from 1919, and in Brazil, mainly from 1976.